2008
DOI: 10.1021/ja806391k
|View full text |Cite
|
Sign up to set email alerts
|

Flexible (Breathing) Interpenetrated Metal−Organic Frameworks for CO2 Separation Applications

Abstract: A breathing 2-fold interpenetrated microporous metal-organic framework was synthesized with a flexible tetrahedral organic linker and Zn(2) clusters that sorb CO(2) preferably over N(2) and H(2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
187
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 427 publications
(193 citation statements)
references
References 20 publications
4
187
0
2
Order By: Relevance
“…The uptake of CO 2 by IFP-7 at 298 K and 1 bar is 40 cm 3 g À1 (7.85 wt%) which is higher than those of the previously reported flexible zinc MOFs with tetrahedral linkers. 25 A similar high uptake was recently found by Yaghi and co-workers for ZIF-69 and ZIF-82, which were synthesized by using imidazolates containing the functional groups Cl and CN. 26 At 195 K, a steep increase in the CO 2 uptake takes place in the low-pressure region (10-110 mmHg), and a small hysteresis is visible in all the desorption branches.…”
supporting
confidence: 79%
“…The uptake of CO 2 by IFP-7 at 298 K and 1 bar is 40 cm 3 g À1 (7.85 wt%) which is higher than those of the previously reported flexible zinc MOFs with tetrahedral linkers. 25 A similar high uptake was recently found by Yaghi and co-workers for ZIF-69 and ZIF-82, which were synthesized by using imidazolates containing the functional groups Cl and CN. 26 At 195 K, a steep increase in the CO 2 uptake takes place in the low-pressure region (10-110 mmHg), and a small hysteresis is visible in all the desorption branches.…”
supporting
confidence: 79%
“…The regeneration energy cost to utilize these porous materials for CO 2 capture by the implementation of temperature swing adsorption, pressure swing adsorption (PSA) and vacuum swing adsorption is significantly lower than the abovementioned alkanolamine technology. More importantly, the rapid development over the past decade in this research field to target some porous MOFs for their extremely high uptake of CO 2 at high pressure 11,12 and to immobilize functional sites, such as open metal sites [13][14][15][16][17][18][19][20][21][22][23] , -NH 2 and -OH organic sites into the pore surfaces to enhance their interactions and thus enforce their efficient CO 2 separation selectivity have principally ensured the feasibility of porous MOFs for CO 2 capture [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] .…”
mentioning
confidence: 99%
“…3 Bae et al synthesized a mixed-ligand MOF, Zn 2 (NDC) 2 (DPNI) [NDC ϭ 2,6-naphthalenedicarboxylate, DPNI ϭ N,N=-di-(4-pyridyl)-1,4,5,8-naphthalene tetracarboxydiimide], and found that this material shows a selectivity of ϳ30 for CO 2 over CH 4 by using the ideal adsorbed solution theory (IAST). 6 Demessence et al synthesized an air-and water-stable MOF, H 3 [(Cu 4 Cl) 3 -(BTTri) 8 ] (H 3 BTTri ϭ1,3,5-tris(1H-1,2,3-triazol-5-yl)benzene). 13 Their results proved that the CO 2 uptakes of this material reach 142.56 mg/g at 298 K and 1 bar, while exhibiting significantly higher uptakes of CO 2 at even lower pressure after functionalized by ethylenediamine.…”
mentioning
confidence: 99%